Utilization of typha-boards for preserving the historic wooden houses typical of the region in the Thai city of Chiang Mai (Thailand) - M. Krus; K. Klingler; St. Bichlmair; Ralf Kilian (Journal of Asian Architecture and Building Engineering, 2025)
The quality of life in the historic wooden houses typical of the city of Chiang Mai in northern Thailand is significantly reduced by climate changes and the intense air pollution during the Haze Season (time of slash-and-burn). The traditional indirect cooling system through strong natural infiltration ventilation in traditional houses is severely limited in its function due to changes in the local urban microclimate. The low comfort level leads to increased use of electric air conditioning, resulting in substantial energy consumption and the formation of urban heat islands and more and more often to the loss of historic Thai wooden houses by demolition.